2006
DOI: 10.21236/ada462018
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Laser-Doppler Velocimeter for Turbulence: Structural Measurements in Turbulent Boundary Layers

Abstract: Public reporting burden for this collection of Informalton Is ealnmated to average 1 hour per response, including the time for reviewing Instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of infomaion. Send comments regarding this burden estimate or any other aspect of this collection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…The result would produce a particle-image displacement pattern after taking into consideration of image magnification and time delay. The river flow velocity will be obtained using the two cameras in a stereoscopic arrangement allowing a visualization of a full field three-dimensional visualization (Le Coz et al, 2010;Lowe, 2006). By employing the PIV water measuring technique, the surface flow velocity from any water channel can be easily measured.…”
Section: Introductionmentioning
confidence: 99%
“…The result would produce a particle-image displacement pattern after taking into consideration of image magnification and time delay. The river flow velocity will be obtained using the two cameras in a stereoscopic arrangement allowing a visualization of a full field three-dimensional visualization (Le Coz et al, 2010;Lowe, 2006). By employing the PIV water measuring technique, the surface flow velocity from any water channel can be easily measured.…”
Section: Introductionmentioning
confidence: 99%
“…The CompLDV probe was developed by Lowe [25]. This system was designed to use up to 12 beams to measure velocity fluctuations as well as velocity-acceleration correlations and velocity gradients, however only six beams were used during the present work.…”
Section: Compldv Probementioning
confidence: 99%
“…Signal processing was done electronically using in-house codes developed by Lowe, [25]. The codes included different modules for burst recognition, dual-burst separation and frequency processing, [26].…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…All work presented in this thesis is on nominally two-dimensional turbulent boundary layers. High free-stream turbulence studies on three-dimensional boundary layers will be done in the future and may be found in Lowe (2006).…”
mentioning
confidence: 99%